In Vitro Stability of Phytase from Recombinant Bacteria E. Coli BL21 (DE3) EAS1-AMP - Adi M.P. Nuhriawangsa; Sajidan Sajidan; Zaenal Bachruddin; Ali Wibowo (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2011)
The objective of the research was to inquire the Km, Vm, activity, intracellular phytase stability exposed to pH variation, temperature variation and protease (pepsin and pancreas) in vitro. The phytase was produced from recombinant bacteria E. coli BL21(DE3) EAS1-AMP using 1.5 mM IPTG as inducer. Intracellular enzyme was extracted via freeze shock and centrifugation. Pure enzyme was acquired through NI-NTA agarose column. The enzyme was then tested for Km, Vm, phytase activity and stability against pH, temperature and protease. Treatment levels for stability against protease were P0: without protease, P1: addition of pepsin, P2: addition of pepsin and pancreas, and the data were statistically analyzed using analysis of variance of one-way Completely Randomized Design. Crude intracellular phytase had Vm 6.39 υM/sec, Km 34.82 υM, and 277 units activity. Intracellular phytas was stable at pH 4–6 and 0–550 C. Protease level influenced the activity of intracellular phytase (P<0.05). Intracellular phytase was stable against pepsin but not pancreas.